EMPOWERMENT OF VILLAGE COMMUNITIES IN PROCUREMENT OF ROAD INFRASTRUCTURE IN PEMATANG KUING VILLAGE, SEI SUKA DISTRICT, BATU BARA REGENCY - Khairunnisa Khairunnisa; Jhon Simon; Rahman Tahir (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Abstract This study aims to analyse community empowerment in the procurement of road infrastructure in Pematang Kuing Village, Sei Suka Sub-district, Batu Bara Regency. Road infrastructure plays a vital role in improving accessibility, supporting economic activities, and strengthening rural welfare. Following the implementation of Law No. 6 of 2014 on Villages, rural communities are positioned as subjects of development who are encouraged to participate actively in every stage of village development, including planning, execution, and maintenance of road infrastructure. The study uses a qualitative approach with a descriptive case-study design. Data were collected through in-depth interviews, participatory observation, documentation, and field notes. Informants were selected through purposive and snowball sampling, comprising the Village Head, village officials, the Village Consultative Body (BPD), community leaders, and beneficiary residents directly involved in road development. Data were analysed using the interactive model of Miles and Huberman. The findings show that community empowerment in road procurement is realised through participation in village deliberation, the involvement of local labour through gotong royong and labour-intensive programmes, and community engagement in monitoring and maintenance. Supporting factors include strong social capital, the Village Fund policy framework, and communicative village leadership. Inhibiting factors comprise budget limitations, technical constraints, and suboptimal management capacity. The study concludes that strengthening institutional capacity, transparency, and meaningful participation is essential for sustainable road infrastructure outcomes at the village level. Keywords: Community Empowerment; Community Participation; Village Road Infrastructure; Village Fund; Sustainable Village Development